Changing Assessment for active learning in an Algebra course - Alfredo Soeiro (2022)
The course takes place in a Civil Engineering Integrated Master program. It has three hours of theoretical classes and two hours of practical classes each week. The contents are the usual of Algebra engineering courses. The assessment method used previously were two tests during the semester followed by exams to improve final grades or to have the chance of replacing failing grades. The percentage of success in the previous years was between 50% and 60%. Several reasons were presented as causes for these low rates of success. It was decided to innovate the assessment while trying to involve students along the semester. The upgrade consisted in including an evaluation of each student along the semester valued at 15% of the final grade. Each student was called randomly at least two times during the semester to solve on the board the problems assigned for each practical class and answer four questions during the theoretical sessions. This allowed to detect understanding problems of students, to motivate students to be prepared for each class and to value the work done along the semester besides the written tests.